Analisis Potensi Dan Kendala Pengembangan Asuransi Jiwa Pada PT. Sunlife Financial Cabang Kota Medan - Manik, M. Bay Hakqi; Syahriza, Rahmi (Jurnal Manajemen Akuntansi (JUMSI), 2021)
Until now the people of Indonesia still have a low level of understanding and awareness of insurance, and among those who have insurance, most do so because of circumstances or circumstances forced.Many insurance companies are eyeing the upper class because the upper class is more aware of the importance of insurance than the lower class. If this paradigm is allowed to continue to grow in society, the development of insurance will remain slow.This research was conducted at PT.Sunlife Financial Medan City Branch on January 17 to February 17, 2022 using library research method.The data collection techniques carried out are observation methods, interviews and accessing internet sites.Life insurance is preferred for the backbone of the family or for those who already have dependents despite not having a family.Based on the results of the analysis that has been done by the author, some conclusions obtained from this study are: the potential of PT. General Takaful Insurance Medan branch in terms of strength Strengh) and opportunity (Opportunity) is a good claim service, easier and faster.Constraints owned by PT. Sun Life Financial Medan City Branch in terms of weakness (Weakness) and threat (threat) is the amount of competition in the insurance industry both from sharia and conventional insurance,